Deciphering Microbiome Related to Rusty Roots of Panax ginseng and Evaluation of Antagonists Against Pathogenic Ilyonectria - Liu, Defei; Sun, Huanjun; Ma, Hongwu (Frontiers in Microbiology, 2019)
Plant roots host diverse microbes that are closely associated with root fitness. Currently, the relationship between microbes and rusty roots of Panax ginseng remains unclear. Here, we described the root-associated microbiome in rusty and healthy ginseng by metagenomic sequencing of 16S rRNA and ITS regions. Being enriched in Diseased-roots (Dr) of ginseng and their rhizosphere soil, the fungus of Ilyonectria, was identified as the most probable cause of the disease after ITS analysis. Meanwhile, an increase of Mortierrella was observed in Healthy-roots (Hr). Surprisingly, an enriched Fusarium was found in both Hr and their rhizosphere soil. Besides, in comparison with Hr, decreased relative abundance of Actinomycetales and increased relative abundance of Pseudomonadales was observed in Dr after 16S rRNA analysis. What’s more, we isolated several microorganisms as antagonists that showed strong inhibiting effects on Ilyonectria in plate assays. In field trials, inoculation of Bacillus sp. S-11 displayed apparent suppression effect against Ilyonectria and shifted microbial communities in rhizosphere soil. Our research identified key microbiota involved in rusty roots of P. ginseng and offered potential biocontrol solutions to rusty disease.